Penulisan dan Publikasi Artikel Ilmiah bagi Guru-Guru SMA Negeri 1 Mayong - Kartinah Kartinah; Noviana Dini Rahmawati; Sutrisno Sutrisno; Muhtarom Muhtarom; Lukman Harun (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The problem faced by partners is that many teachers still have difficulty in compiling scientific papers and publishing them in the form of national journals. Based on the partners' problems above, the solution we offer is to train and assist teachers in compiling scientific articles to journal publications. This training activity is designed in stages, starting with a classical meeting in the form of a seminar with introductory material on scientific publications, preparation of scientific articles and journal publications. After completing the theory, the practice of making scientific articles is carried out with direction and guidance from the service team. The conclusion from the training activities for writing and publishing scientific articles, the teachers at SMA Negeri 1 Mayong are very enthusiastic in participating in this training activity because many teachers, both young and senior teachers, still have difficulty writing scientific articles and then publishing them. Even though the publication of scientific articles is one of the points that can be used to improve the rank of teachers. Because of the enthusiasm of the teachers' enthusiasm for learning, the training activities for writing and publishing scientific articles at SMA Negeri 1 Mayong can be carried out well and the teachers have been able to compile scientific articles and submit them to national journals.